Problematika ICC Dalam Menjatuhkan Sanksi Kepada Israel Dalam Perspektif Hukum Internasional - Agung Tri Wicaksono; Achmad Arbi’ Nur Badrotin Jabbar; AH. Fajruddin Fatwa (Pusat Riset dan Inovasi Nasional, 2024)
The International Criminal Court (ICC) or International Criminal Court is a court that is not under the United Nations (UN) and is independent and has jurisdiction to try a person/country suspected of committing serious human rights crimes such as war crimes, genocide and crimes. towards humans. However, in reality, the ICC seems to ignore acts of genocide and war crimes committed by Israel against Palestine on the pretext that Israel does not recognize the Rome Statute and is not a member of the ICC, so Israel cannot be subject to any sanctions from the ICC. The aim of this research is to examine and explore why the ICC seems to be ignoring Israel's actions, which should be under its jurisdiction. The method used in this research is juridical/normative legal research with the Roman Statute as the primary legal material. The findings of this research are that Israel should still be subject to sanctions by the ICC based on article 12 paragraph 2 of the Rome Statute which states that the ICC's jurisdiction also applies to non-ICC countries that commit crimes in the territory of countries that recognize the Rome Statute, in this case Palestine has ratified the Statute. Rome on April 1 2015. The implication of this research is that Israel can be tried by the ICC even though they have not ratified the Rome Statute.